Customized Titanium Mesh for Guided Bone Regeneration in the Posterior Mandible in a Patient Previously Treated with Bisphosphonates - Johannes Müller; Rüdiger Junker (Hindawi Limited, 2022)
We describe the restorative treatment of an 86-year-old female patient who was referred to our specialist prosthodontics clinic. Due to secondary osteoporosis, she underwent oral antiresorptive therapy with ibandronic acid for 10 years. Although she was classified as a patient at increased risk of drug-induced osteonecrosis of the jaw, she eventually signed a consent form for fixed implant-supported prosthetic rehabilitation in her 4th sextant. However, after tooth extraction, the bone ridge was too small at the intended implant positions. Therefore, guided bone regeneration was performed with a computer-aided design/computer-aided manufacturing three-dimensional printed titanium mesh. Finally, a continuous augmented hard tissue ridge above 7 mm was found, and three implants were inserted. Eventually, after four months of submerged healing, the implants were loaded with single crowns. Now, the patient is seen regularly for supportive peri-implant therapy.